Language, public space and an educated imagination - Dasgupta, Probal (2004)
When we try to associate linguistics with educational reform, we need some care about what reform means. Its default reference to the market is hard to unpack. Who should count as education's customer is crucially unclear. If education is an investment in human resources becomes too narrow. The public's collective interest is at stake. The state or its advisory bodies cannot learn from linguistics or other rapidly developing fields. Such learning has to be done by active participants in the public debate process. The arena to be reshaped through this debate is the public space itself. -Reproduced.
Keywords: Education